2014
DOI: 10.1039/c4ay00424h
|View full text |Cite
|
Sign up to set email alerts
|

New insights on blue pigments used in 15th century paintings by synchrotron radiation-based micro-FTIR and XRD

Abstract: The blue pigments used on altarpieces in 15 th Century in Catalonia and Crown of Aragon are principally the azurite mineral. To a lesser extent lapis lazuli, also of mineral origin and occasionally, in the background areas, outlining the figures, and for the chromatic ground layer, indigo, were used. Data from several altarpieces belonging to well-known artists of the time is presented. Synchrotron radiation X-ray diffraction (SR-XRD), micro-infrared spectroscopy (µ-FTIR), synchrotron radiation micro-infrared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 19 publications
0
31
0
Order By: Relevance
“…Salvadó et al made a multitechnique microanalysis of the blue paints in different altarpieces in Catalonia and Crown of Aragon from the 15th century, identifying lapis lazuli, azurite and indigo. Veneranda et al identified the compounds constituting a mural painting in the Assumption's church of Alaiza in Basque Country, Spain, and investigated the degradation induced by agricultural activities.…”
Section: Introductionmentioning
confidence: 99%
“…Salvadó et al made a multitechnique microanalysis of the blue paints in different altarpieces in Catalonia and Crown of Aragon from the 15th century, identifying lapis lazuli, azurite and indigo. Veneranda et al identified the compounds constituting a mural painting in the Assumption's church of Alaiza in Basque Country, Spain, and investigated the degradation induced by agricultural activities.…”
Section: Introductionmentioning
confidence: 99%
“…cm −1 region, which could be linked to an overlapping of Al, Si-O4 tetrahedra symmetric stretching vibration of lazurite and O-Si-O symmetric stretching vibration of wollastonite [61]. The band at 568 cm −1 and the band at 452 cm −1 represent the terminal -O-Si-Obonds bending vibration and Si-O-Si bending vibration, respectively [62][63][64]. The visible spectrum of the lapis lazuli was dominated by an absorption band around 600 nm, corresponding to the electronic transitions for S3 − (see Figure 3g).…”
Section: Chalkmentioning
confidence: 94%
“…The FTIR spectra showed bands in the 1100-900 cm −1 region that could be assigned to overlapping of Al, Si-O 4 tetrahedra asymmetric stretching vibration of lazurite and O-Si-O asymmetric stretching vibration of wollastonite, as well as bands in the 700-600 cm −1 region, which could be linked to an overlapping of Al, Si-O 4 tetrahedra symmetric stretching vibration of lazurite and O-Si-O symmetric stretching vibration of wollastonite [61]. The band at 568 cm −1 and the band at 452 cm −1 represent the terminal -O-Si-Obonds bending vibration and Si-O-Si bending vibration, respectively [62][63][64].…”
Section: Lapis Lazulimentioning
confidence: 95%
“…XRD and SR-FTIR proved to be especially useful. The application of several layers with decreasing particle size, starting with azurite and finishing with lapis lazuli relates these artworks van Eyck's ''Adoration of the Mystic Lamb'' [196]. Synthetic ultramarine shares many properties with its natural form.…”
Section: Pigment Degradation Studies Related To Fifteenth-seventeenthmentioning
confidence: 99%